Double-hit and double-protein-expression lymphomas: aggressive and refractory lymphomas. Issue 15 (November 2015) - Sarkozy, Clémentine; Traverse-Glehen, Alexandra; Coiffier, Bertrand
Summary: Double-hit lymphoma (DHL) is a subgroup of aggressive lymphomas with both MYC and BCL2 gene rearrangements, characterised by a rapidly progressing clinical course that is refractory to aggressive treatment and short survival. Over time, the definition was modified and now includes diffuse large B-cell lymphoma (DLBCL) with MYC translocation combined with an additional translocation involving BCL2 or BCL6 . Some cases that have a similar clinical course with concomitant overexpression of MYC or BCL2 proteins were recently characterised as immunohistochemical double-hit lymphomas (ie, double-protein-expression lymphomas [DPLs]). The clinical course of these DPLs is worse than so-called standard DLBCL but suggested by some studies to be slightly better than DHL, although there is overlap between the two categories. Present treatment does not allow cure or long-term survival in patients with genetic or immunohistochemical double-hit lymphomas, but several new drugs are being developed.